Microfresamento de aço inoxidável duplex UNS S32205 com ferramentas de metal duro revestidas com nitreto de titânio - Santos, Aline Gonçalves dos (2016)
The development of technology in many areas has increased the demand for production of components with small dimensions. In this scenario, the micro machining has emerged as an important tool because it is a process with great precision in producing micro-scaled components. This technique allows processing of composites, polymers, ceramics, and metallic alloys, including stainless steels. Stainless steels are popular due to their chemical characteristics like high resistance to corrosion and oxidation. The main goal of this work is the study of phenomena involved in micromilling a UNS S32205 duplex stainless steel, using TiN coated carbide tools. Accordingly, it was investigated tool wear type and mechanism, burr formation and machined surface quality. For this purpose, this work was carried out with a 4-axis CNC micromill machine tool using 0.381 mm diameter tools. Pre-tests were carried out in order to select the most appropriate cutting condition for further analysis. Tool wear, machined surface and burr were examined in a scanning electron microscope. The burr height and roughness were measured by a profilometer. The results show that the major forms of wear are nose and flank wear, with predominance of the adhesion wear mechanism. The wear land as a function of machined length showed similar behavior to macro machining operations with three well defined regions of different wear rates. Taylor s equation was obtained and the coefficients are similar to those obtained in conventional operations. It was observed that the top burr presented the most significant size. The results obtained for the surface roughness, Ra, varied in the range of 0.131 to 0.469 μm.